Research Progress in Biodiversity and Human Well-Being, Based on CiteSpace - Sunbowen Zhang; Linsheng Wen; Aifang Weng; Dongliang Cheng; Baoyin Li (Biology)
Biodiversity is crucial for human well-being and economic prosperity, representing a significant factor in constructing a global community of life on Earth. This study focuses on 4453 articles indexed in the Web of Science Core Collection, employing the visualization analysis software Citespace 6.2.R7 for bibliometric analysis of research related to biodiversity and human well-being. The findings indicate the following: (1) there is a steady increase in publications on biodiversity and human well-being, covering 167 disciplinary fields, indicating a broad research scope; (2) the literature spans 168 countries and regions, with major contributions from the United States, England, Germany, Australia, and China; (3) COSTANZA R is the most cited author in this field, with Science being the most recognized journal; and (4) current research hot topics include ecosystem services, genetic diversity, marine protected areas, nature-based solutions (NbS), and green spaces, while climate change, urban green space management, and national park system development are identified as important emerging directions. This study, grounded in significant global literature, aims to enrich the breadth and depth of research on biodiversity and human well-being, offering feasibility references for constructing theoretical frameworks in biodiversity studies and providing theoretical guidance for promoting modern harmonious coexistence between humans and nature.